Permasalahan Clinical Coding Pada Sistem Casemix Penyebab Pending Claim Pasien Jaminan BPJS Di Rumah Sakit X - Santoso, Sugeng; Markus, Suryo Nugroho; Ningsih, Kori Puspita (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda (JIPIKI), 2026)
Background: Clinical coding accuracy is a vital factor in the financial stability of hospitals under the BPJS Health casemix system. Errors in clinical coding frequently lead to pending claims, which hinder the hospital's cash flow. Objective: This study aims to analyze the underlying causes of casemix coding issues in pending claims for BPJS Health patients at Hospital X. Method: This research employed a descriptive analytical method with a qualitative approach. Data were collected through in-depth interviews with five informants, consisting of two clinical coders, one casemix coordinator, and two physicians, as well as document observations of medical records and claim regulations. Result: The findings indicated a pending claim rate of 10.2%, with 33.3% of these cases caused specifically by clinical coding errors. The primary causes were categorized into three factors: (1) Human Resources, involving low coder competency in ICD-10/9-CM guidelines and medical pathognomonics; (2) Documentation Process, including incomplete medical resumes and a lack of clinical evidence provided by physicians; and (3) System, characterized by the infrequent socialization of the latest claim regulations and technical agreements. Conclusion: Accuracy in casemix coding is highly dependent on the synergy between comprehensive clinical documentation and the coder's expertise. Hospitals are recommended to implement continuous professional training and routine medical audits to minimize financial risks.